'Protecting the Primitive Natives': Indigenous People as Endangered Species in the Early Nature Protection Movement, 1900-1940. (1st August 2015) - Sysling, Fenneke
Abstract : This paper draws attention to the role of indigenous people in the early nature protection movement in Europe. In the first half of the twentieth century, not only flora and fauna but on several occasions 'natural people' too were the object of the protection ambitions of nature conservationists. In discussions on the history of nature protection much attention has been paid to the ways indigenous people were separated from the nature in which they lived, while today they are often portrayed as ideal guardians of nature. However their complex position in the movement as endangered species themselves has been overlooked. This paper addresses this issue by examining the Swiss naturalist Paul Sarasin's calls for the protection of indigenous people in the 1910s and the campaign of the Netherlands-based Committee for International Nature Protection in the 1930s to establish a reserve to protect the inhabitants of the highlands of New Guinea. These episodes in the history of nature protection show how shared communities of scientific expertise and their concepts of endangerment produced a continuum between 'nature' and 'natural people' in early conservation discourse that was then mobilised into protection schemes.